Online purchase order system using Android application : a review - Hashim, Nik Mohd Zarifie; Raveendhran, Thirumalni; Salleh, Azahari; Ab Hadi, Nik Azran; A Aziz, Khairul Azha; Mohamad, Najmiah Radiah (Research India Publications, 2015)
Research on online order purchase system application has been quite improved in the past years. The difficulties faced by this application are some of the applications do not have different types of payments and it had less function button in the application. Rather than that, some of the applications not have a proper database that linked directly to bothclient and owner. Hence, in the present study, an online purchase order system using interface of Android based application were purposed. This purposed application have a proper database system that link user to server interface, and have a system that can link smart phone to online ordering software. The application that purposed can be used in electronic product and component selling business by using android smart phone with internet connection. The outcome from this application is to create user-friendly software that can easily do online ordering and can easily link with database and smart phone.